A CFD Study on the Design Optimization of Airborne Infection Isolation Room. (3rd October 2022) - Le, Thanh-Long; Nguyen, Tan Tien; Kieu, Trung Tin
Abstract : Airborne infection isolation (AII) rooms are used to accommodate patients with highly infectious diseases and keep the released pathogens to limit the risk of cross-infection. This paper proposes a concept for an AII room made from two shipping containers to handle the scarcity of hospital beds when the COVID-19 disease spreads over the world. The proposed system consists of the main isolation room, anteroom, and toilet as well as other functional areas. In addition, the main isolation room was modeled with important components such as a supply air vent, exhaust air, a patient, and a bed. The computational fluid dynamics (CFD) approach based on the finite volume method (FVM) is used to solve the three-dimensional governing equations. The CO2 concentration was used to determine the infectious contaminant concentration of the air in the room. Therefore, the infectious control could be evaluated by the air change per hour (ACH). The numerical results show that the room temperature is maintained at 24°C, which is appropriate for people in the room. The laminar airflow extends downward to the floor after leaving the supply air vent on the ceiling, creating circulating patterns throughout the room. When evaluating the effectiveness of ventilation systems to remove airborne contaminants based on different ACH numbers, the CO2 concentration in the room was reduced to 581 ppm, 477 ppm, and 438 ppm in the cases of 12 ACH, 24 ACH, and 48 ACH, respectively. As a result, the greater the number of air change per hour, the greater the performance for contaminant removal. It served as the foundation for assessing and optimizing the ventilation system of the portable negative pressure room.